2021
DOI: 10.3390/jcm10051030
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Tranexamic Acid in Emergency Trauma: A Systematic Review and Meta-Analysis

Abstract: In trauma patients, bleeding can lead to coagulopathy, hemorrhagic shock, and multiorgan failure, and therefore is of fundamental significance in regard to early morbidity. We conducted a meta-analysis to evaluate the efficacy and safety of tranexamic acid (TXA) in civil and military settings and its impact on in-hospital mortality (survival to hospital discharge or 30-day survival), intensive care unit and hospital length of stay, incidence of adverse events (myocardial infarct and neurological complications)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 48 publications
(88 reference statements)
0
10
0
1
Order By: Relevance
“…Several meta-analyses have been done to explore the risk and benefits of TXA in trauma [ 20 23 ]. These meta-analyses, however, contain few studies on prehospital administration of TXA [ 1 , 20 ], whereas most were conducted in the hospital settings [ 21 , 23 26 ]. Evidence indicates that TXA reduces death secondary to bleeding by as much as 32% if given within 1 h of injury, but may increase death if given after 3 h [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several meta-analyses have been done to explore the risk and benefits of TXA in trauma [ 20 23 ]. These meta-analyses, however, contain few studies on prehospital administration of TXA [ 1 , 20 ], whereas most were conducted in the hospital settings [ 21 , 23 26 ]. Evidence indicates that TXA reduces death secondary to bleeding by as much as 32% if given within 1 h of injury, but may increase death if given after 3 h [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although TXA has a half-life of 2.3 h in adult patients [ 29 ], one study showed that in one-fifth of cases, a single dose of TXA given en route to the hospital did not attain adequate plasma level measured at hospital admission [ 27 ]. Moreover, TXA administration may increase the risk of thromboembolic complications, particularly when higher or repeated doses are used as shown in the MATTERS and HALT-IT trials [ 21 , 30 , 31 ]. Moreover, there are few studies on the efficacy and safety of TXA en route to the hospital or at the scene [ 20 , 32 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…This systematic review and meta-analysis were performed under the preferred reporting items for systematic review and meta-analysis (PRISMA) guidelines [14]. This study represents a continuation of prior research on the use of TXA previously undertaken by the authors [15,16].…”
Section: Methodsmentioning
confidence: 99%
“…Tranexamic acid (TXA) is a low molecular antifibrinolytic drug [1] that has been used for many years to control hemorrhage in patients with hemophilia and other disorders involving coagulation system. The particular interest in TXA use was initially found by its ability to control massive hemorrhages in the prehospital setting, especially in the tactical environment, due to a statistically significant reduction of risk of death, when used in the early stage of pharmacotherapy [2][3][4]. The search for the safe and effective drug, which may be used in the prehospital control of hemorrhage is related to the epidemiology of injuries and its impact on the mortality of the overall population.…”
Section: Introductionmentioning
confidence: 99%